Synergistic enhancement of toughness and antibacterial properties of plant cellulose/glycerin/chitosan degradable composite membranes. Issue 2 (21st September 2020) - Yin, Longfei; Yin, Fengwei; Huang, Dan; Zheng, Weilong; Li, Lan; Fu, Yongqian
Abstract: BACKGROUD: With the development of modern industry, the task of replacing ordinary plastic products with environmentally friendly antibacterial materials is a high priority. In this study, natural cellulose from sugarcane was compounded with glycerin and chitosan to prepare a cellulose/glycerin/chitosan (CGC) degradable composite membrane with antibacterial properties. The physical and chemical structure of the CGC composite film was characterized by X‐ray diffraction, scanning electron microscopy, thermogravimetric analysis and mechanical testing. Then antibacterial properties of CGC composite membranes were measured. RESULTS: The data showed that the raw materials used in the composite film had interacted showing the compatibility of the three components. The addition of chitosan and glycerin can improve the toughness of cellulose‐based membranes. The samples CGC‐5/2, CGC‐10/2 and CGC‐15/2 showed four‐, three‐ and 2.7‐fold greater elongation at break, respectively, than with the cellulose membrane. Hygroscopic and water solubility test showed that the higher the chitosan content, the greater the water absorption of the composite membrane and the weaker the water solubility. However, the higher the glycerin content, the weaker the hygroscopicity of the CGC composite membrane and the greater its water solubility. Additionally, the antibacterial performance of the CGC composite membrane was significantly improved and the glycerin:chitosan ratio affects its antibacterial ability against different bacteria. CONCLUSIONS: This research provides a low‐cost and green method for preparing antibacterial film, which can be applied to environmentally friendly packaging films, medical films and electronic product encapsulation films. © 2020 Society of Chemical Industry (SCI)